Effect of Disinfection with Spraying Technique 35 % Betel Pepper leaf boiling water and 0,5 % Sodium Hypochlorite on Dimensional Stability of Casts Made from Alginate - Durrotul Lamiah; R Rahardyan Parnaadji; Agus Sumono (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Alginate is an impression matter that often used on dentistry. Some studies showed that aginate caused cross infection. it needs a disinfection product to avoid that cross infection. the disinfection matter which often used are betel pepper leaf boiling water and the sodium hypochlorite, but alginate have imbibition characteristic and fenol that contain in betel pepper leaf boiling water suggested dimensional changes on alginate. The technique of this research with sprayed technique. The aim of this research’s to find dimentional stability on casts made from alginateafter disinfection procedure with sprayed technique used 35 % betel pepper leaf boiling water and 0,5 % sodium hypochlorite. This research is an experimental laboratories using post test only control group design. The samples are an upper jaw replica. The samples are 28 samples and divided into 4 groups. A group is directly filling and the others are sprayed with aquadest sterile, 35 % betel pepper leaf boiling water and 0,5 % sodium hypochlorite and saved in vacuum box for 10 minutes. Samples measured by term mizzen with 0,05 accuracy.The conclusion of this research is there was dimentional changes on casts made from alginate after disinfection procedure with sprayed technique used 35 % betel pepper leaf boiling water and 0,5 % sodium hypochlorite. Keywords: Alginate, betel pepper leaf, cross infection, dimensional stability, sodium hypochlorite.